2015
DOI: 10.5152/npa.2015.7477
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Repeated Botulinum Toxin Treatment for Sialorrhea in Patients with Parkinson’s Disease

Abstract: Repeated injections of BoNT-A are safe and effective in treating sialorrhea in patients with PD. Based on our results, it seems that there is a maintenance of efficacy after a three-year period and an increase in the mean duration of efficacy with the number of injections. Further prospective clinical studies with larger number of patients and more longer duration of follow-up are needed to confirm our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Accordingly, striking structural abnormalities of neuromuscular junctions and intramuscular nerves were more pronounced after repetitive injections. Moreover, in human therapeutic BoNT-A application, more distinct and longer lasting effects, resulting in an increase in the mean duration of efficacy with the number of injections are well known [ 41 , 42 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, striking structural abnormalities of neuromuscular junctions and intramuscular nerves were more pronounced after repetitive injections. Moreover, in human therapeutic BoNT-A application, more distinct and longer lasting effects, resulting in an increase in the mean duration of efficacy with the number of injections are well known [ 41 , 42 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among all the salivary glands, the parotid gland is the major target when injecting botulinum toxin in all studies, and can be treated alone [6,7,16] or, what happens in most studies [3,10,14,15,17,18], along with the submandibular glands, since both produce 90% of total saliva. There are two studies [4,19] that do not specify into which gland the treatment is applied.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the adverse effects, it should be noted that in three studies no side effects were highlighted, in two of them nothing was specified in that regard, and in the rest of cases in which an alteration occurred, this was of a mild nature, for example viscous saliva, dry mouth, difficulty in the motor control of tongue, skin reaction and aggravation of previous dysphagia. [4,7,13,14,15,16,26,27,28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…86 Retrospective analysis of patients in a movement disorders clinic showed that all patients treated with BoNT-A experienced improvements; a minimum of 50% improvement in sialorrhoea was observed using the Drooling Severity and Frequency Scale (DSFS). 87 The majority of PD outpatients completing an RCT reported satisfaction with BoNT treatment [moderate to dramatic improvement (77.7%; n = 18)] compared with placebo [no changes to mild improvement (94.4%; n = 18)]. 83 All patients receiving BoNT injections stated that they would receive repeated injections.…”
Section: Current Treatment Options For Sialorrhoeamentioning
confidence: 99%